2016
DOI: 10.17795/ojcr-7242
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Zinc Sulfate on Subfertility Related to Male Factors: A Prospective Double-Blind, Randomized, Placebo-Controlled Clinical Trial

Abstract: Background: Different studies found that zinc is necessary for sexual maturity, growth and fertility. But there are no distinct studies that clarify the role of zinc supplements on semen parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Zinc sulfate in a dose of 66 mg taken together with folic acid 5 mg a day for 26 weeks by the subfertile patients after varicocelectomy has been shown to significantly increase the percentage of spermatozoa with normal morphology at months 3 and 6 23 . Zinc sulfate administered as solution 5 mg × 3 times daily (15 mg) for 3 months has been shown to very slightly increase the percentage of sperm cells with normal morphology, 32 but much higher daily dose of zinc (220 mg for 4 months) with 5 mg folate showed no benefits 33 . A systematic review and meta‐analysis of the trials assessing a role of zinc and folic acid concluded about improvement of sperm morphology 34 .…”
Section: Discussionmentioning
confidence: 99%
“…Zinc sulfate in a dose of 66 mg taken together with folic acid 5 mg a day for 26 weeks by the subfertile patients after varicocelectomy has been shown to significantly increase the percentage of spermatozoa with normal morphology at months 3 and 6 23 . Zinc sulfate administered as solution 5 mg × 3 times daily (15 mg) for 3 months has been shown to very slightly increase the percentage of sperm cells with normal morphology, 32 but much higher daily dose of zinc (220 mg for 4 months) with 5 mg folate showed no benefits 33 . A systematic review and meta‐analysis of the trials assessing a role of zinc and folic acid concluded about improvement of sperm morphology 34 .…”
Section: Discussionmentioning
confidence: 99%
“…After removal of duplicates, 29,325 articles were obtained, of which 29,067 were excluded, because they were deemed not relevant based on title and/or abstract reading. Thus, as shown in Figure 1, a total of 258 articles were identified, of which 29 RCTs, involving 2,045 men (mean age: 33.5 years) with oligo, astheno‐ and/or teratozoospermia, met the inclusion criteria 35–63 . In particular, we excluded five trials by Safarinejad, 64–68 as the reliability of their results could not be guaranteed due to the large number of papers retracted by this author (http://retractiondatabase.org/RetractionSearch.aspx#?auth%3dSafarinejad).…”
Section: Resultsmentioning
confidence: 99%
“…All participants had at least one abnormality in standard semen parameters (oligo‐, astheno‐ and/or teratozoospermia). Sperm concentration was investigated in 15 RCTs, 35,38,40,41,44,45,47,49,50,53,54,58,61–63 total sperm motility in 21 RCTs, 35–37,39,41–44,47,49,50,52,53,55,57–61,63 sperm progressive motility in 14 RCTs, 35–40,42,45,46,48–51,54,56 and sperm morphology in 14 RCTs 35,38,40,44,46,47,49,50,54–56,58,61,63 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation